Insights from a qualitative study of the procurement and manufacture of active pharmaceutical ingredients in India - Hamill, HM; Hampshire, K; Vinaya, H; Mamidi, P (BMJ Publishing Group, 2023)
Medicine supply systems are a crucial part of health systems and access to effective essential medicines is a key pillar of Universal Health Coverage. However, efforts to expand access are compromised by the proliferation of substandard and falsified medicines. The vast majority of research to date on medicine supply chains has focused on the formulation and distribution of the finished product, overlooking the crucial steps of Active Pharmaceutical Ingredient production that precede this. In this paper, we draw on qualitative interviews with manufacturers and regulators in India to take a ‘deep dive’ into these understudied parts of medicine supply chains.